Gender and heresy : women and men in Lollard communities, 1420-1530 - McSheffrey, Shannon (Middle Ages series., 1995)
Shannon McSheffrey studies the communities of the late medieval English heretics, the Lollards, and presents unexpected conclusions about the precise ways in which gender shaped participation and interaction within the movement.